Bipolar disorder: the neglected psychosis - Bhagwagar, Z; Goodwin, G (2007)
Bipolar disorder is a chronic, severe and disabling illness which levies a significant toll on the individual, family and society in general. The pathophysiology of the illness remains to be clarified though elegant work done recently highlights the role of intracellular signalling pathways and monoaminergic transmission. The illness is defined by discrete episodes of mania and, almost invariably, depression and, of course, patients can present in either of the two poles of illness. Therapeutic interventions for patients need to be tailored to the stage of illness and take account of the fact that patients may already be on drug treatment. Antipsychotics, lithium and valproate all have anti-manic actions shown in randomized controlled trials (RCTs). Treatment of depressive episodes can be challenging given the relative lack of effective treatments. Lithium has long been regarded as the gold standard for long-term treatment while lamotrigine has been shown to have efficacy in preventing episodes of bipolar depression. While pharmacotherapy should be considered the mainstay of treatment for bipolar disorder, there is an emerging role for non-pharmacological interventions, especially in the maintenance of euthymia. © 2007 Elsevier Ltd. All rights reserved.